Saccharomyces cerevisiae UE-ME3 a wild-type strain of Alentejo, Portugal, reveals an adaptive response to phenylurea herbicide isoproturon - Candeias, M (2011)
The phenylurea isoproturon (IPU), 3-(4-isopropylphenyl)-1,1-dimethylurea, widely used as an active compound of several herbicides, is absorbed by the roots and leaves, where it acts at the level of electron transport chain of chloroplast, behaving as an inhibitor of photosynthesis. In plants exerts its toxic action mainly by competing with plastoquinone and in this context with the D1 protein of photosystem II present in the tilacoidal membrane. Therefore, the presence of IPU in the eukaryotic cells can generate ROS and consequently oxidative stress. The European Union has listed IPU as one of the 33 special substances that threaten the earth surface because it exhibits low water solubility and chemical/biological degradation. So it can accumulate in soils as waste and therefore persists in biological systems for long periods. In addition, it may be involved in triggering of serious illnesses like cancer. In spite of this, it is urgent to find microorganisms and methods which would help to eliminate the environmental contaminations of this phenylurea. The main purpose of this study was to evaluate the response to IPU by wine wild-type Saccharomyces cerevisiae UE-ME3, deposited in the collection of Enology Laboratory of University of Évora, Portugal, grown in the YEPD medium.